2016
DOI: 10.1074/jbc.m116.740571
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of Zeste Homolog 2 Inhibition Stimulates Bone Formation and Mitigates Bone Loss Caused by Ovariectomy in Skeletally Mature Mice

Abstract: Perturbations in skeletal development and bone degeneration may result in reduced bone mass and quality, leading to greater fracture risk. Bone loss is mitigated by bone protective therapies, but there is a clinical need for new bone-anabolic agents. Previous work has demonstrated that Ezh2 (enhancer of zeste homolog 2), a histone 3 lysine 27 (H3K27) methyltransferase, suppressed differentiation of osteogenic progenitors. Here, we investigated whether inhibition of Ezh2 can be leveraged for bone stimulatory ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 53 publications
9
106
1
Order By: Relevance
“…Beyond studies from our own group [Dudakovic et al, 2016; Dudakovic et al, 2015b; Dudakovic et al, 2013; Farzaneh et al, 2016], other studies have used various screening methods to assess expression and function of epigenetic regulators. These studies utilized technologies such RNA interference [Bajpe et al, 2015; Cellot et al, 2013; Fazzio et al, 2008], high-content cell-spot microarrays [Bjorkman et al, 2012], as well as large-scale reverse genetic screening [Huang et al, 2013] to screen for epigenetic regulators in various tissues, organism, and disease states.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Beyond studies from our own group [Dudakovic et al, 2016; Dudakovic et al, 2015b; Dudakovic et al, 2013; Farzaneh et al, 2016], other studies have used various screening methods to assess expression and function of epigenetic regulators. These studies utilized technologies such RNA interference [Bajpe et al, 2015; Cellot et al, 2013; Fazzio et al, 2008], high-content cell-spot microarrays [Bjorkman et al, 2012], as well as large-scale reverse genetic screening [Huang et al, 2013] to screen for epigenetic regulators in various tissues, organism, and disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Using the method we described here in detail, we identified the H3K27 methyltransferase EZH2 as the most prominently down-regulated epigenetic regulator during osteogenic commitment of MSCs [Dudakovic et al, 2015b]. Our group and others collectively showed that EZH2 is a principal epigenetic regulator of osteogenic lineage commitment of MSCs and a suppressor of osteoblast maturation [Dudakovic et al, 2016; Dudakovic et al, 2015b; Hemming et al, 2014; Hui et al, 2014; Wei et al, 2011]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations